Upin Ipin reading kit / Nursyahmina Zainal Abidin and Sumarni Maulan - Zainal Abidin, Nursyahmina; Maulan, Sumarni (Academy of Language Studies, 2023)
Cartoons are not simply created for entertainment among children, but they are also a tool for education purposes. This project is about the creation of a reading kit using characters from the Upin Ipin animation series. The aim is to create a reading kit based on the Upin Ipin characters. There are five stages of this project completion: word selection and story writing, Les’ Copaque consent application, layout designing and product printing, children’s observation, and a survey on the product. It can be concluded that the project is a tremendous success with the end product triumphantly produced and the children in a kindergarten showed keen interest in the product during the observation. The survey also received favourable responses from the respondents as they agree with the choice of design and layout, contents, and usefulness of the product. It is hoped that this product will be able to help children learn English vocabulary by drawing their interest to their favourite cartoon characters, Upin Ipin.